U–Pb SHRIMP zircon dating and geochemistry of metapelites from the Shillong Meghalaya Gneissic Complex, NE India: Implications for nature of protolith and tectonic setting - Shyam Bihari Dwivedi; Pratigya Pathak; Kevilhoutuo Theunuo; Ravi Ranjan Kumar (Geosystems and Geoenvironment, 2023)
The Sonapahar area of Shillong Meghalaya Gneissic Complex (SMGC) is an extension of the Central India Tectonic Zone within the Precambrian Indian shield. The study area mainly consists of metapelites, basic granulites, granitic gneisses and high-grade gneisses as metamorphic imprints. U–Pb SHRIMP zircon dating yields a late Paleoproterozoic age of 1672 ± 6 Ma, which is age of the metapelites protolith. The petrochronology and geochemistry of metapelites and granitic gneiss basement rocks have been studied to learn more about the SMGC's tectonic environment, involvement in the supercontinent cycle, crustal development and geodynamic context. In the NCKFMASHTO system, phase equilibria modelling of metapelites shows peak metamorphic stage at P-T conditions of 8.25 kbar/ 820 °C. Cordierite is formed during retrograde metamorphism during the decompression phases. The negative anomalies in Nb, Sr and Ti indicate that crustal sources played a significant role in magmatic emplacement. Geochemical data from metapelites indicate that protoliths were trachy-andesitic in nature, generated during the syn-orogenic environment by subduction tectonism. The SMGC experienced significant tectonic activity throughout the Paleoproterozoic age when the subduction tectonic setting coincided with orogenic activity. The presence of Paleoproterozoic age in the study area, as well as Southwestern Australia and East Antarctica correlates the Sonapahar granulite with the Columbia supercontinent history.